THE IMPACT OF CORONA DISEASE OUTBREAK ON THE EXISTENCE OF PERSONAL PROTECTIVE EQUIPMENT SURGICAL MASKS IN THE MOJOKERTO REGENCY AND CITY EAST JAVA - Imam Baidlowi (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2020)
This study focuses on the existence of personal protective equipment surgical masks in the community of Mojokerto Regency and City. The problem is the difficulty of finding Personal Protective Equipment Surgical masks that meet the health standards which are needed by the community but are very difficult to find and buy. The purpose of study is to find out the cause of people's difficulty finding personal protective equipment in the form of surgical masks, as well as to know there is a relation between covid 19 news and the loss of protective equipment in the form of surgical masks, to know what is the cause of the loss of personal protective equipment surgical masks on the market. The results showed that difficult to find the personal protective equipment surgical masks or out of stock that have been sold in pharmacies, pharmacies do not get supplies from supplier. According to the manufacturer that in April 2020 the production of surgical masks for national needs has been excessive and can be exported as well and according to the head of the pharmacist association in Indoneseia in East Java Province, that the stock needs masks at the district and city level in East Java is enough. But the reality until the end of this study on May 12, 2020, researchers repeated to the pharmacy turns out that in pharmacies researchers have not found a surgical mask. There are people who sell surgical masks but not pharmacies but in the market that is not clear how to buy them through order to someone with prices up 335% to 340% of the price before the covid-19 pandemic.